Answer :
For this case we have the following equation:
[tex]F = \frac {mv ^ 2} {r}[/tex]
We must clear the value of the variable v:
Multiplying by "r" on both sides we have:
[tex]rF = m * v ^ 2[/tex]
Dividing between "m" on both sides:
[tex]\frac {rF} {m} = v ^ 2[/tex]
Applying square root to both sides:
[tex]v = \pm \sqrt {\frac {rF} {m}}[/tex]
Thus, the solutions are:
[tex]v_ {1} = \sqrt {\frac {rF} {m}}\\v_ {2} = - \sqrt {\frac {rF} {m}}[/tex]
Answer:
[tex]v_ {1} = \sqrt {\frac {rF} {m}}\\v_ {2} = - \sqrt {\frac {rF} {m}}[/tex]